The Synaptic Vesicle Protein 2A Interacts With Key Pathogenic Factors in Alzheimer’s Disease: Implications for Treatment - Kong, Yanyan; Huang, Lin; Li, Weihao; Liu, Xuanting; Zhou, Yinping; Liu, Cuiping; Zhang, Shibo; Xie, Fang; Zhang, Zhengwei; Jiang, Donglang; Zhou, Weiyan; Ni, Ruiqing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer’s Disease (AD), a serious neurodegenerative disease, is pathologically characterized by synaptic loss and dysfunction. Synaptic vesicle protein 2A (SV2A) is an indispensable vesicular protein specifically expressed in synapses and can be used as a biomarker for synaptic density. Nevertheless, the involvement of SV2A in the pathogenesis and development of AD and its relation to other hallmarks of AD pathology, such as amyloid precursor protein (APP), β-amyloid (Aβ), and tau protein are not fully understood we found the expression of SV2A was downregulated in the hippocampus of AD patients. In addition, SV2A colocalized with APP and was downregulated at Aβ deposition. Moreover, we used APPswe293T cells lines to either silence or overexpress SV2A and found that SV2A deficiency leads to a simultaneous increase in Aβ and Tau hyperphosphorylation, while SV2A overexpression was associated with down-regulation of BACE1 and APOE. In addition, evidence gained in the study points PI3K signaling pathway as a possible mediator in SV2A regulation influencing the incidence and development of AD. With limited effective diagnostic methods for AD, close interplay between SV2A and AD related proteins demonstrated in our study may provide novel and innovative diagnostic and therapeutic opportunities.